2013
DOI: 10.1098/rspb.2013.1124
|View full text |Cite|
|
Sign up to set email alerts
|

Male age mediates reproductive investment and response to paternity assurance

Abstract: Theory predicts that male response to reduced paternity will depend on male state and interactions between the sexes. If there is little chance of reproducing again, then males should invest heavily in current offspring, regardless of their share in paternity. We tested this by manipulating male age and paternity assurance in the burying beetle Nicrophorus vespilloides. We found older males invested more in both mating effort and parental effort than younger males. Furthermore, male age, a component of male st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 54 publications
(117 reference statements)
2
48
0
Order By: Relevance
“…Specifically, old males produced significantly fewer offspring than young males in control treatments, but elevated their reproductive success to similar levels as young males after treatment (young males did not alter their reproductive effort across treatments). In addition to age (Sanz et al 2001;Copeland and Fedorka 2012;González-Tokman et al 2013), other studies provide support for context-dependent terminal investment through significant interactions between treatment levels of a terminal investment trigger (e.g., immune stimulation) with a number of other factors, including genotype (Chadwick and (Krams et al 2015), and paternity assurance (Benowitz et al 2013). In our study, old males show terminal investment, but young males do not.…”
Section: Discussionsupporting
confidence: 64%
“…Specifically, old males produced significantly fewer offspring than young males in control treatments, but elevated their reproductive success to similar levels as young males after treatment (young males did not alter their reproductive effort across treatments). In addition to age (Sanz et al 2001;Copeland and Fedorka 2012;González-Tokman et al 2013), other studies provide support for context-dependent terminal investment through significant interactions between treatment levels of a terminal investment trigger (e.g., immune stimulation) with a number of other factors, including genotype (Chadwick and (Krams et al 2015), and paternity assurance (Benowitz et al 2013). In our study, old males show terminal investment, but young males do not.…”
Section: Discussionsupporting
confidence: 64%
“…At dispersal, larvae were counted and weighed individually to 1 mg. At each check, we recorded the location of the parent. Cessation of parental care by a beetle is characterized by its continuous absence at a location away from the carcass, and is a readily recognizable behaviour regardless of the type of observation chamber used (Benowitz et al, 2013(Benowitz et al, , 2015Hopwood et al, 2015;Parker et al, 2015). As in these previous studies, when a beetle was observed to be away from the carcass for three consecutive observations, and thus persistently absent over a 24-h period, we defined it as abandoned.…”
Section: Methodsmentioning
confidence: 99%
“…Our analyses emphasize that the differences in total allelic metrics between current and future broods are compound quantities, which depend not only on the relative degrees of female extra-pair reproduction and consequent paternity loss, but also on brood sizes and on the kinship between the male and his socially-paired females and her extra-pair males. Four variables consequently affect the relative allelic metrics of males' current versus future broods, even without considering the male's probability of surviving to future reproductive events, or any other dimension of variation in offspring value stemming from differential life-history trade-offs or environmental or maternal genetic effects (e.g., Westneat and Sherman 1993;Eliassen and Kokko 2008;Benowitz et al 2013). Although a male's own f also influences allelic metrics, f is a fixed property of an individual male and therefore cannot contribute to within-male variation in brood values.…”
Section: Reproduction and Inbreedingmentioning
confidence: 99%
“…Meanwhile, a male's kinship with his socially-paired female's current versus future extra-pair males will depend on the female's extra-pair reproductive strategy and on the availability of male relatives of the focal male, which will in turn depend on the male's previous within-pair and extra-pair reproductive success and that of his relatives (e.g., Reid et al 2015b). It may therefore be difficult for individual males to "predict" the total allelic value or carrier probability of future versus current broods and modulate paternal care accordingly, unless key causal variables vary systematically with predictable aspects of male state such as age (e.g., Benowitz et al 2013). Future analyses should quantify the pattern and magnitude of variation in total allelic metrics across consecutive broods reared by individual males in song sparrows and other systems.…”
Section: Reproduction and Inbreedingmentioning
confidence: 99%
See 1 more Smart Citation